A Configurational Causation in Post–Arab Spring Political Economy: Regime Transition Modes and Economic Liberalization in the Middle East (2011–2024) - La Ode Sugianto; Sinthia Nurhabibah; Hariya Toni; Hisyam Syafii; Salma Dzakiyyah Az Zahrah; Husain Azhari (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2026)
This study examines how modes of political regime transition shape economic liberalization trajectories in six Middle Eastern states: Tunisia, Egypt, Libya, Morocco, Jordan, and Algeria, across the post-Arab Spring period from 2011 to 2024. Drawing on comparative historical analysis, the study challenges linear assumptions linking democratization to market reform, arguing instead that the outcomes of economic liberalization are determined by the configurational interaction of three causal conditions: transition modality (revolutionary overthrow, negotiated settlement, or authoritarian adaptation), distributional coalition alignment, and institutional capacity. Rather than treating regime type as a singular independent variable, the analysis shows that no single condition is sufficient to explain divergent liberalization trajectories; it is the specific combination and sequencing of these conditions that produce distinct policy outcomes across cases. Revolutionary transitions in Tunisia and Egypt created structural openings for reform but simultaneously destabilized the institutional scaffolding required for consistent policy implementation. By contrast, monarchical continuity in Morocco and Jordan enabled selective, gradual liberalization insulated from distributional conflict. Across all six cases, trade liberalization advanced most consistently, while privatization and subsidy reform faced organized resistance from labor coalitions and middle-class constituencies. Institutional capacity, operationalized through bureaucratic professionalization, central bank autonomy, and judicial effectiveness, emerged as a critical intervening mechanism that moderated the translation of political transition into economic policy change. External conditionality from international financial institutions further shaped reform sequencing, with domestic coalitions exercising selective compliance as a strategic response. The findings yield a configurational causal framework applicable to post-authoritarian political economies in the Middle Eastern regional context and contribute to broader theoretical debates on the sequencing of simultaneous political and economic liberalization.